1995
DOI: 10.1007/bf00196368
|View full text |Cite
|
Sign up to set email alerts
|

Occurrences of dendritic gold at the McLaughlin Mine hot-spring gold deposit

Abstract: Abstract. Two styles of gold dendrites are variably developed at theMcLaughlin Mine. The most abundant occurrence is hosted by amber-coloured hydrocarbon-rich opal. Silica likely precipitated from a boiling hydrothermal fluid and complexed with immiscible hydrocarbons forming an amorphous hydrocarbon-silica phase. This phase likely scavenged particulate gold by electrostatic attraction to the hydrocarbon-silica phase. The dendritic nature of the gold is secondary and is the result of dewatering of the amorphou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Therefore, the dendritic aggregates of palladian gold appear to be only weakly affected by weathering, and are more likely residual components of a primary, hydrothermal mineralization. In this connection, it is worth mentioning that dendritic gold is known to occur in epithermal and hot-spring gold deposits (Saunders 1994, Sherlock & Lehrman 1995. Also, the dendritic aggregates of Pt-Pd and Pd-Hg-Au alloys from the Bom Sucesso stream, Minas Gerais, possibly result from open-space infill by low-temperature hydrothermal fluids (Cassedanne et al 1996, Fleet et al 2002.…”
Section: Dendrites Of Palladian Goldmentioning
confidence: 99%
“…Therefore, the dendritic aggregates of palladian gold appear to be only weakly affected by weathering, and are more likely residual components of a primary, hydrothermal mineralization. In this connection, it is worth mentioning that dendritic gold is known to occur in epithermal and hot-spring gold deposits (Saunders 1994, Sherlock & Lehrman 1995. Also, the dendritic aggregates of Pt-Pd and Pd-Hg-Au alloys from the Bom Sucesso stream, Minas Gerais, possibly result from open-space infill by low-temperature hydrothermal fluids (Cassedanne et al 1996, Fleet et al 2002.…”
Section: Dendrites Of Palladian Goldmentioning
confidence: 99%
“…Although perhaps best evident in LS epithermal deposits from Nevada, Idaho, and Washington of the western USA such as those discussed here, gold/electrum nanoparticles might also be locally important in some bonanza epithermal ores such as in Japan [5][6][7][8][9][10] and elsewhere in western USA such as McLaughlin, California [26], and the Sunnyside gold mine [46] of the Silverton district, San Juan Mountains, Colorado. High-grade Sunnyside ores contained discrete electrum/gold-rich depositional events that also appear to have formed by colloid aggregation (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Thus in the newer terminology those "fractal" dendrites were made from electrum nanoparticles as opposed to colloids. Others have interpreted the origin of "fractal" dendrites in bonanza epithermal gold ore to be the result of diffusion of gold in silica gels [26]. Do gold (or naumannite) nanoparticles have different physical properties than gold colloids, and do nanoparticles of gold as they are transported up?…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to this colloform quartz, bands composed of other textural types of quartz are barren. Similarly, Sherlock and Lehrman [76] demonstrated that colloform bands in crustiform veins from the McLaughlin deposit in California consist of compacted microspheres of quartz that formed through recrystallization of a noncrystalline silica precursor phase. The bands contain gold as dendrites or as particles that are concentrated in the interstitial space between the microspheres.…”
Section: Implications For Ore-forming Processesmentioning
confidence: 91%
“…Fluid inclusion evidence from Buckskin National in Nevada [40,42], Sleeper in Nevada [79], McLaughlin in California [76,80], Guanajuato in Mexico [14,81], and Koryu in Japan [17] is interpreted to indicate that phase separation of the hydrothermal liquids occurred during vein formation, even though the exact conditions of noncrystalline silica deposition cannot be ascertained due to the lack of primary fluid inclusions in the colloform bands composed of relic microspheres. Additional evidence for the occurrence of boiling at these deposits includes the presence of platy calcite which is replaced by quartz pseudomorphs (cf.…”
Section: Implications For Ore-forming Processesmentioning
confidence: 99%